Evaluation of properties in different casings modified by surfactants and lactic acid using terahertz spectroscopy – A feasibility study. (September 2021) - Feng, Chao-Hui; Otani, Chiko; Ogawa, Yuichi; García-Martín, Juan F.
Abstract: The spectra change of sausage hog and sheep casings before and after casing modification in the terahertz range were obtained using a terahertz time-domain spectroscopy (THz-TDS) system. Casings were modified by a surfactant solution (composed of soy lecithin and soy oil) and lactic acid, and the water content, swelling ratio and thickness of original and modified casings were determined. THz absorbance spectra of casings were acquired by THz-TDS in the range of 0.5–3.5 THz in attenuated total reflectance (ATR) mode. The absorbances of terahertz spectra for modified hog and sheep casings were greatly higher than that without modification. The THz spectra changes of casings were monitored by THz-TDS using the shift time between low and high frequencies in the ATR system. The drying time under nitrogen gas at 20 L/min flow rate was 31.62 min for natural hog casing. The results demonstrate the potential of THz-TDS to determine aforementioned parameters of original and modified casings as well as other foodstuffs during drying process. Highlights: High-water-content food material was for the first time applied to terahertz spectroscopy (THz). THz spectra changes of different types of casings before and after modification were verified. The evolution of spectra changes in fresh natural hog casing during drying was innovatively illustrated by THz. A qualitative relationship between casing drying process and THz spectra was demonstrated. The absorbances of THz spectra for modified hog and sheep casings were greatly higher than fresh ones.